SEBERANG Ilir’S MUSICAL CONCEPT IN SYAROFAL ANAM’S PERFORMANCE AT TWELVES NIGHT IN THE CITY OF PALEMBANG - Sastra, Andar Indra; Ediwar, Ediwar (CAIJ: Creative Arts Interdisciplinary Journal, 2022)
This paper aims to reveal the musical concept of Seberang Ilir in the Syarofal Anam at nighttwelve in Palembang City. The musical concept of Seberang Ilir appears in technical terms relatedto Pengawak Hadi, Hadi Penjawab, and Rodat being an essential part of the vocal elements anddancer movements. In addition, from the position of the musicians known as musicians of thePenabuh Umak, Ningkah-Ngulung, and Mecah/Ngana’i. Pengwak Hadi means bearer of Hadi,meaning a person who is trusted to bring Shalawatan (priest) in the Syarofal Anam performance.Answering Hadi is a technical term for the role of a supporter of neurologist Anam, that is,intending to reply to the vocals of the Hadi singer; and Rodat ‘s poems Syarofal AnamUmak is aperson or group that plays a fixed rhythm (tempo control) on a Terbangan instrument Terbanganpattern of basic. Ningkah is a pattern of flying rhythms beat whose shape gives a shout from theUmak or intersperses the Umak; Ningkah Mecah rhythm patterns wasp marry. Ngulung is avariation of the Tepukan Terbangan pattern Mecah and rhythm or Ngana’I is a partner pattern ofNgulung. The problems discussed in this paper include the formation of the musical concept ofSeberang Ilir in the Syarofal Anam at night twelve in Palembang city.Keywords: Musical Concept, Seberang Ilir, Syarofal Anam, Twelfth Night, Palembang